Decolonising Ethics : considerations of power, politics and privilege in Aotearoa/New Zealand - Boulton, Amohia (Southern African Journal of Social Work and Social Development, 2018)
Indigenous peoples across the world have a shared experience of colonisation; a process that has resulted in war, disease and the decimation of their lands, homes and peoples. In New Zealand, the effects of colonisation are still evident with Māori (the indigenous people of New Zealand) experiencing poorer outcomes compared with non-Māori citizens across a range of social, health and well-being indicators. This paper is a case study of work being done in New Zealand, which may have resonance with work in South Africa, and other countries with a history of colonisation. It begins with a brief history of the impacts of colonisation on Māori before considering the concept of decolonisation. The author outlines the work her organisation does as an independent, tribally owned, Māori health research centre to advance a decolonisation agenda. Reflecting on their emancipatory and democratising ambitions as researchers provides the opening for a discussion about indigenous ethics. The paper presents a number of Māori ethical principles that guide their work, arguing that were such principles applied in the development and implementation of social policy and legislation, the effect would be a fairer, more equitable policy that better meets the needs of Māori as citizens. Recent legislation enacted to improve New Zealand’s care and protection system for children is discussed to illustrate the need for greater consideration of Māori values when developing legislation that directly impacts Māori. The paper concludes with a challenge to policymakers, practitioners, academics, and researchers alike to actively contribute to an agenda of liberation, emancipation and decolonisation for indigenous peoples.
Keywords: Care and protection; Care ethics; Decolonisation; Indigenous ethics; Māori; Self-Determination

Māori and Pasifika leaders’ experiences of government health advisory groups in New Zealand - Came, Heather; McCreanor, Tim; Haenga-Collins, Maria; Cornes, Rhonda (Kōtuitui: New Zealand Journal of Social Sciences Online, 2019)
Māori and Pasifika populations in New Zealand experience poorer health outcomes than other New Zealanders. These inequalities are a deeply entrenched injustice. This qualitative study explores the experiences of six Māori and Pasifika leaders on health policy-making advisory committees. All had extensive experience in the health system. They were recruited, provided semi-structured interviews, the data coded, and a thematic analysis undertaken. Our findings show that inequalities in the health system are reproduced in advisory committees. Participants noted their knowledge and interests were devalued and they experienced racism and tokenistic engagement. Some indicated it took considerable effort to establish credibility, be heard, have impact, and navigate advisory meetings, but even then their inputs were marginalised. Health policy advisory committees need deeper engagement and more genuine recognition of Māori and Pasifika knowledge. Māori and Pasifika leaders have constructive solutions for eliminating health inequities that could benefit all New Zealanders.
Keywords: Māori; New Zealand; Pasifika; health policy; racism

The politics of reconciliation in New Zealand - Sullivan, Ann (Political Science, 2016)
Reconciliation in New Zealand involves recognition, reparations and an apology for past injustices relating to breaches of the Treaty of Waitangi. In 1840, Māori and the British Crown signed a treaty that promised a beneficial relationship to both signatories. Almost immediately after the Treaty was signed and continuing through to today, promises inherent in the principles of the Treaty have been breached. However, in 1975, a government-appointed permanent commission of inquiry was established to investigate actions or omissions of the Crown that breach the promises made in the Treaty of Waitangi. The Waitangi Tribunal and the Ministry of Justice provide the institutional mechanisms used in New Zealand to foster reconciliation. This article will discuss how the state has moved iwi from being in Treaty ‘grievance mode’ to one of tino rangatiratanga/Māori self-determination and demonstrates how reconciliation has integrated Treaty settlement iwi into the mainstream New Zealand economy.
Keywords: Indigenous rights; Māori; politics; reconciliation; treaty

Barriers to and opportunities for the restoration of mana in emergency management legislation and its implementation for Māori - Reid, John; Awatere, Shaun; Rout, Matthew; Campbell, Emily; Huang, Annie; Warmenhoven, Tui (Disasters, 2025)
Ever since colonisation by the British in 1840, Māori, the indigenous peoples of Aotearoa New Zealand, have been fighting to reclaim their mana (authority and influence) over their whenua (land). They were set to regain mana in emergency management (EM) through a parliamentary Bill, but a recent change of government has seen this legislation discharged. This paper explores the barriers to and the opportunities for gains in authority and influence in EM, with authority understood as representation on the national and regional EM bodies, and influence as incorporation of the Māori worldview into legislation and supporting EM implementation documentation. The study applies these different levels of analysis to two case studies to examine any EM-related changes between the Christchurch earthquake in February 2011 and the arrival of Cyclone Gabrielle in February 2023. The paper offers several strategies at both analytical levels that Māori could use to further their mana under the current government.
Keywords: Aotearoa; Māori; New Zealand; disaster risk reduction; emergency management; legislation

Region-level Pākehā warmth towards Māori enhances collective action intentions: An extension of the social identity model of collective action (SIMCA) - Houkamau, Carla; Bahamondes, Joaquín; Osborne, Danny; Sibley, Chris (International Journal of Intercultural Relations, 2024)
New Zealand is a peaceful nation, but ongoing political tensions and inequities between Māori (the indigenous peoples of New Zealand) and Pākehā (the majority group of Europeans) persist as a result of its colonial history. Identifying ways to redress the enduring legacy of colonialism are therefore of critical importance. Accordingly, this paper examines data from 7017 Māori, as well as 37,233 Pākehā, to examine the impact of regional-level Pākehā warmth towards Māori on Māori support for progressive collective action. Results reveal that Pākehā warmth towards Māori varies markedly across 257 regional wards (regional units created for New Zealand electoral purposes). Moreover, multilevel modelling demonstrates that Pākehā warmth towards Māori at the region-level correlates positively with Māori identity and political efficacy at the individual level which, in turn, both correlate positively with collective action support. Collectively, these results demonstrate the impact of the broader social climate on social change, while identifying a previously-unknown facilitator of collective action support (namely, a broader context of warmth towards structurally disadvantaged groups).
Keywords: Activism; Māori; Political rights; Social identity model of collective action (SIMCA)

Indigenous Representational Choices: Results from a Large Qualitative Survey on Māori Electoral Roll Choice - Greaves, Lara Marie; Hini, Rebecca; Overbye, Hannah R.; Brink, Kaylee Grace (Journal of Race, Ethnicity, and Politics, 2025)
Different participatory mechanisms for the representation of Indigenous peoples have been proposed across states. Since their creation in 1867, the Māori electorates in the national Parliament have led to dedicated representation for Māori (Indigenous peoples of New Zealand). However, only half of Māori choose to vote on the Māori roll, the remainder choosing to vote on the General roll, illustrating that roll choice is not based simply on group representation. This survey aimed to ask Māori (N = 1,958) in their own words why they made their roll choice. Through a deductive codebook thematic analysis, a range of codes were constructed around the reasoning behind roll choice. Māori on the Māori roll made their choice because they valued Māori representation; as an expression of their identity; to support the electorates; as a strategic choice; or they had been influenced by others or through education. Those on the General roll felt their roll was the default or a more familiar option; the Māori roll had less of an impact; it was a strategic choice, or they appreciated greater candidate variety; or they valued the smaller geographic electorate size. Some felt Māori no longer needed separate representation or felt less connected to their identity as Māori. The results have implications for both Māori and Indigenous representation through dedicated representational mechanisms.
Keywords: Indigenous; Māori; Māori electorates; Voting; Parties; Parliament; representation; voter enrolment

Māori Linked Administrative Data: Te Hao Nui - A novel Indigenous Data Infrastructure and Longitudinal Study - Boulton, Amohia; Theodore, Reremoana; Sporle, Andrew (The International Indigenous Policy Journal, 2023)
Worldwide, large amounts of administrative data are collected within official statistics systems on Indigenous Peoples. These data are primarily used for government and state policy purposes as opposed to by Indigenous Peoples to support Indigenous agendas (Taylor & Kukutai, 2017). In Aotearoa me Te Waipounamu New Zealand, Māori need high quality data to develop evidence-based policies and programs and to monitor government policies that impact on Māori. In this methodological paper, we describe uses of administrative data for Māori and current barriers to its use. We outline the development of a novel administrative data infrastructure and future longitudinal study. By explicating our Indigenous initiated, designed and controlled data project, we make a methodological contribution to Indigenous Data Sovereignty and Kaupapa Māori (Māori worldview) epidemiology.
Keywords: Indigenous data sovereignty; Māori; administrative data; policy; wellbeing; youth

Hauora hinengaro o takatāpui: analysing the effectiveness of mental health policies in addressing the needs of Takatāpui in Aotearoa New Zealand - Benvie-Watson, Emma; Greaves, Lara M. (Culture, Health & Sexuality, 2024)
Many studies have documented the effect that colonisation has had on takatāpui, that is, Māori (the Indigenous peoples of New Zealand) with diverse gender identities, sex characteristics and sexualities. In this paper, we explore whether current Aotearoa New Zealand (hereafter Aotearoa) mental health policies meet the needs of takatāpui. We identified five mental health policy needs, informed by the literature. We then explored policy documents from government ministries, district health boards and non-government organisations to see the extent to which policy met these needs. Four themes were present in the literature analysed: an overall lack of acknowledgment of takatāpui and intersectionality; promising engagement with the needs of takatāpui by NGOs; symbolic commitment to Te Tiriti o Waitangi; and some limited engagement with Māori health models. The findings show promise in some areas but demonstrate a lack of engagement by policy to meet the needs of takatāpui.
Keywords: Identity & Intersectionality; Mental health; Māori; Policy; Takatāpui